Overload effect revisited − Investigation by use of configurational forces. (February 2016) - Ochensberger, W.; Kolednik, O.
Graphical abstract: Highlights: Configurational force concept provides new insight into the overload effect. Cyclic incremental plasticity J -integral Δ J actPZ ep describes overload effect. The major mechanism is the reduction of stresses around the growing crack tip. Effects of residual stresses and crack flank contact on overload effect separated. The delayed retardation phenomenon is investigated. Abstract: The configurational force concept enables the derivation of the incremental plasticity J -integral J ep, which is, in contrast to the conventional J -integral, physically appropriate to characterize the crack driving force in cyclically loaded elastic–plastic materials with growing cracks. In this paper we apply J ep, combined with an analysis of the configurational force distribution, for the investigation of fatigue crack growth retardation after a single tensile overload. The motivation for this investigation is that the main reason for the overload effect, i.e. crack flank contact behind or residual stresses around the growing crack tip, is today still an open question in fatigue. Numerical case studies are performed for two-dimensional Compact Tension specimens with long cracks that grow under cyclic Mode I loading and plane strain conditions. Variables of the numerical case studies are the overload ratio and the load ratio during constant cyclic loading. The influence of crack flank contact is examined by a comparison of two different simulations: The first simulation assumes frictionless contact between the upper and lower crack flank; in the second, fictive case, it is assumed that crack flank overlap is possible. The results show that all features of the overload effect even occur, if crack flank contact is not possible. Finally, the ability of the effective stress intensity range Δ K eff to characterize the overload effect is also discussed.